Celiac disease diagnosis still significantly delayed – Doctor's but not patients' delay responsive for the increased total delay in women. Issue 10 (October 2016) - Vavricka, Stephan R.; Vadasz, Nina; Stotz, Matthias; Lehmann, Romina; Studerus, Diana; Greuter, Thomas; Frei, Pascal; Zeitz, Jonas; Scharl, Michael; Misselwitz, Benjamin; Pohl, Daniel; Fried, Michael; et al.
Abstract: Background: There is insufficient data on diagnostic delay and associated factors in celiac disease (CeD) as well as on its potential impact on the course of disease. Methods: Specifically taking its two components – patients' and doctors' delay – into account, we performed a large systematic patient survey study among unselected CeD patients in Switzerland. Results: We found a mean/median total diagnostic delay of 87/24 months (IQR 5–96), with a range from 0 up to 780 months and roughly equal fractions of patients' and doctors' delay. Both mean/median total (93.1/24 vs. 60.2/12, p  < 0.001) and doctors' (41.8/3 vs. 23.9/2, p  < 0.001) diagnostic delay were significantly higher in female vs. male patients, whereas patients' delay was similar, regardless of preceding irritable bowel syndrome diagnosis. Patients with a diagnostic delay shorter than 2 years were significantly less often in need of steroids and/or immunosuppressants, substitution for any nutritional deficiency but more often free of symptoms 6 and 12 months after diagnosis. Conclusions: There is a substantial diagnostic delay in CeD, which is associated with a worse clinical outcome and significantly longer in female patients. This increased diagnostic delay in women is due to doctors' but not patients' delay and cannot be explained by antecedent IBS prior to establishing the CeD diagnosis.